El Pradito del bienestar emocional: Diseño de experiencias de bienestar laboral para la prevención del Burnout en mujeres profesoras (2024)
Having found that teachers are more exposed to chronic stress and Burnout syndrome, this project developed a strategy to implement wellness experiences to prevent and reduce recurrent work stress in teachers, providing enriching break spaces, such as an emotional nursing that provides the necessary tools to successfully regulate stress, anxiety and frustration, which were the most recurrent emotions of teachers.